Sex Slavery under Domestic and Colonial Patriarchy in Nora Okja Keller’s Comfort Woman (KEMANUSIAAN The Asian Journal of Humanities, 2022)
Sex slavery operated through the comfort women system during World War II has been a historical shame and an inconvenient truth for both the Japanese and the Korean. This study, through Nora Okja Keller’s Comfort Woman, investigates the life of a Korean character forced to become a comfort woman, arguing that domestic patriarchy and colonial patriarchy are the main institutions which transform her into a sex slave. A representation of Korean comfort women, she is exploited by the patriarchal oppression in her family and the Japanese colonial patriarchy. Her body is transformed into a commodity to sustain her family and offer comfort and pleasure to Japanese soldiers. Despite her liberation, she becomes a traumatised subject whose painful memories keep haunting her even when she relocates to the United States. Patriarchal violence in the form of sex slavery has destroyed her life and left a detrimental legacy preventing her from rebuilding a new successful life. The traumatic past causes this character and her daughter to be seen as weird Asians who are “double-othered” in the United States, a new world where they are unable to recover from profound trauma in spite of their new identity as Korean American.